Analysis of Gene Expression in Cyclooxygenase-2-Overexpressed Human Osteosarcoma Cell Lines - Jeong A. Han; Ji-Yeon Kim; Jong-Il Kim (Genomics & Informatics)
Osteosarcoma is the most common primary bone tumor, generally affecting young people. While the etiology of osteosarcoma has been largely unknown, recent studies have suggested that cyclooxygenase-2 (COX-2) plays a critical role in the proliferation, migration, and invasion of osteosarcoma cells. To understand the mechanism of action of COX-2 in the pathogenesis of osteosarcoma, we compared gene expression patterns between three stable COX-2-overexpressing cell lines and three control cell lines derived from U2OS human osteosarcoma cells. The data showed that 56 genes were upregulated, whereas 20 genes were downregulated, in COX-2-overexpressed cell lines, with an average fold-change > 1.5. Among the upregulated genes, COL1A1, COL5A2, FBN1, HOXD10, RUNX2, and TRAPPC2are involved in bone and skeletal system development, while DDR2, RAC2, RUNX2, and TSPAN31are involved in the positive regulation of cell proliferation. Among the downregulated genes, HIST1H1D, HIST1H2AI, HIST1H3H, and HIST1H4C are involved in nucleosome assembly and DNA packaging. These results may provide useful information to elucidate the molecular mechanism of the COX-2-mediated malignant phenotype in osteosarcoma.